The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/ece3.1884
|View full text |Cite
|
Sign up to set email alerts
|

Varying foraging patterns in response to competition? A multicolony approach in a generalist seabird

Abstract: Reducing resource competition is a crucial requirement for colonial seabirds to ensure adequate self‐ and chick‐provisioning during breeding season. Spatial segregation is a common avoidance strategy among and within species from neighboring breeding colonies. We determined whether the foraging behaviors of incubating lesser black‐backed gulls (Larus fuscus) differed between six colonies varying in size and distance to mainland, and whether any differences could be related to the foraging habitats visited. Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 57 publications
5
58
0
1
Order By: Relevance
“…Inter‐ and/or intraspecific competition (Corman et al., 2016; Hamilton, Gilbert, Heppner, & Planck, 1967) may thus be an important factor driving decisions on where to forage. Corman et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Inter‐ and/or intraspecific competition (Corman et al., 2016; Hamilton, Gilbert, Heppner, & Planck, 1967) may thus be an important factor driving decisions on where to forage. Corman et al.…”
Section: Discussionmentioning
confidence: 99%
“…Corman et al. (2016) demonstrated low inter‐ and intracolonial overlaps in foraging behavior in lesser black‐backed gulls. In our study, gulls from Langeness were the most flexible in terms of habitat choice although the sample size of tagged birds from this colony was very low.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One individual observed in this study showed that at least some individual gulls can have alternative migration strategies within their life span. Previously abundant but already declining anthropogenic resources utilized by gulls, such as human refuse and fishery discards (Camphuysen , Camphuysen et al , Corman et al ), are likely to decline further due to changes in EU legislation (Bicknell et al ); whether or not individuals can adapt to these changes within their life span will highly depend on their behavioural plasticity and ability to adapt their foraging or migration strategies accordingly. In order to understand the consequences of different migration strategies and changes within the key resources, they should be considered within the context of the annual cycle and life history of an individual (Harrison et al , Marra et al ).…”
Section: Discussionmentioning
confidence: 99%